2019
DOI: 10.21608/ijma.2019.12703.1005
|View full text |Cite
|
Sign up to set email alerts
|

Clusterin and psoriasis, what is the relation?

Abstract: Background: Psoriasis is a chronic inflammatory immunologically mediated disease characterized by antigen presentation and keratinocytes hyperproliferation due to release of chemokines and cytokines from activated T-lymphocytes. Relationship between psoriasis and peripheral vascular diseases, increased risk of myocardial infarction and cerebrovascular diseases has been reported. Clusterin [apolipoprotein J] is a 75-80 KDa disulfide-linked heterodimeric protein associated with apoptosis and clearance of cellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…This is not consistent with Hashem et al that suggest that serum clusterin levels were higher than controls and suggest the presence of psoriasis-metabolic syndrome pathogenic interactions and with Zhu et al who concluded that serum values of clusterin were increased in the premature form of coronary artery disease. 12,13,15 Comparing between psoriatic patients having metabolic syndrome and psoriatic patients having no metabolic syndrome revealed no significant difference in clusterin serum levels. This matches with Garcia-Rodriguez et al who however said that clusterin levels are decreased in psoriatic patients than controls, but also found that there was no difference in its levels in patients haning and having no metabolic syndrome.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…This is not consistent with Hashem et al that suggest that serum clusterin levels were higher than controls and suggest the presence of psoriasis-metabolic syndrome pathogenic interactions and with Zhu et al who concluded that serum values of clusterin were increased in the premature form of coronary artery disease. 12,13,15 Comparing between psoriatic patients having metabolic syndrome and psoriatic patients having no metabolic syndrome revealed no significant difference in clusterin serum levels. This matches with Garcia-Rodriguez et al who however said that clusterin levels are decreased in psoriatic patients than controls, but also found that there was no difference in its levels in patients haning and having no metabolic syndrome.…”
Section: Discussionmentioning
confidence: 92%
“…With no significant correlation in clusterin level with other studied parameters in all psoriasis cases. 10,13 The results obtained by Garcia-Rodriguez et al observed that plasma clusterin was reduced in psoriasis patients compared with healthy controls but the study had a small sample size. 14 In this study there was a comparison between psoriatic patients with metabolic syndrome and controls where there were differences in correlation to any other parameter.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…HaCaT cells, immortalized human keratinocytes, also produce clusterin 24 . Serum clusterin levels are higher in patients with psoriasis than in healthy controls 25 , 26 , and the clusterin mRNA level in skin lesions from patients with psoriasis is different from that in normal controls 27 . However, little is known about how clusterin affects the inflammatory reactions associated with psoriasis.…”
Section: Introductionmentioning
confidence: 95%